Relationship of Women’s Marital Intimacy with Health Literacy and Attitudes Towards Extramarital Relations of Husbands with Diabetes - Hellinia, Ghazaleh; Homaei, Rezvan (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Given the considerable negative effects of diabetes, improving health literacy can play a deciding role in preventing and treating such diseases and in saving resources. The present study aimed to investigate the relationship between women’s marital intimacy with health literacy and attitudes towards extramarital relations of husbands with diabetes in Ahvaz. Methods: The statistical population of this descriptive correlational study included all the diabetes patients and their wives in Ahvaz in 2021. The sample of 141 men with diabetes and their wives was selected using convenience sampling. To collect data, the Marital Intimacy Scale, Health Literacy for Iranian Adults (HELIA), and Attitudes toward Infidelity Scale (AIS) were used. The Pearson correlation coefficient and regression were simultaneously used for data analysis. Results: The results suggested that health literacy (r= 0.35) and attitudes towards extramarital relations (r= -0.27) in men with diabetes had significant positive and negative correlations with women’s marital intimacy, respectively. The regression results indicated that the variables of health literacy and attitudes towards extramarital relations in men had a significant multiple correlation with women’s marital intimacy (P<0.001). Conclusions: The results illustrated that paying attention to health literacy and attitudes of men with diabetes towards extramarital relations for their wives’ marital intimacy was more important than ever before.